2020
DOI: 10.37985/jer.v1i3.25
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Budaya Sekolah dan Diklat terhadap Kinerja Guru

Abstract: Penelitian bertujuan untuk mengetahui pengaruh budaya sekolah dan Diklat terhadap kinerja guru sekolah dasar. Data penelitian ini dikumpulkan melalui penyebaran kuesioner kepda responden. Hasil angket dianalisis dengan menggunakan analisis regresi berganda melalui uji t, uji F, dan koefisien determinasi. Populasi dalam penelitian ini adalah seluruh guru SD Negeri di Kecamatan Sungai Lilin yang berjumlah 74 orang. Teknik pengambilan sampel yang digunakan adalah purposive sampling. Sampel penelitian adalah 44 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 0 publications
1
6
0
6
Order By: Relevance
“…Workplace climate conducive is perfect fit and support them the education process and teachers. As research of [7] stated that any impact: 1 ) significant schools to culture on teacher performance in public primary schools kecamatan sungai wax; 2 ) any impact to significant a teacher training in public primary schools kecamatan sungai wax any impact; 3 ) significant culture schools and training to on teacher performance together in public primary schools kecamatan sungai wax. Thus , good working environment will make teachers feel secure , comfortable in do teaching and learning activities that teachers can improve the learning and teaching ability to process or be more attractive and able to accomplish a purpose it desirable .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Workplace climate conducive is perfect fit and support them the education process and teachers. As research of [7] stated that any impact: 1 ) significant schools to culture on teacher performance in public primary schools kecamatan sungai wax; 2 ) any impact to significant a teacher training in public primary schools kecamatan sungai wax any impact; 3 ) significant culture schools and training to on teacher performance together in public primary schools kecamatan sungai wax. Thus , good working environment will make teachers feel secure , comfortable in do teaching and learning activities that teachers can improve the learning and teaching ability to process or be more attractive and able to accomplish a purpose it desirable .…”
Section: Resultsmentioning
confidence: 99%
“…Paud that all agencies in indonesia quality can be government institutions has the feasibility assessment quality this authority institutions paud authority held by the national education early childhood and non formal education based on permendikbud no.52 about the year 2015 paud and pnf chapter article 1 verse 1. And 8 which is used to national standard for penyeolengaraan paud education (1) the standard development attainment, (2) the standard, (3), standard process (4) standard, teachers and staff (5) standard of infrastructures , (6) standard management, (7) standard financing and (8) standard education the law the Indonesian government .…”
Section: Introductionmentioning
confidence: 99%
“…This research was also sponsored by Muhammad Dahlan, Yasir Arafat, and Syaiful Eddy 2020. The findings showed that: 1) there was a significant impact of school culture on the performance of teachers in the SD Negeri Sungai Lilin District; 2) there was a significant impact of education and training on the performance of teachers in the SD Negeri Sungai Lilin District; 3) there was a significant impact of school culture and education and training on the performance of teachers in the SD Negeri Sungai Lilin District [21].…”
Section: The Effect Of the Teaching Discipline On The Output Of Teachersmentioning
confidence: 96%
“…The Principal must be able to practice creativity, be able to lead all stakeholders and the school as an educational institution to change their minds, develop their vision and purpose by using the strengths, expertise and abilities of its members. Dahlan et al [5] clarified that school principals are a deciding factor in the management of education in their schools in order to achieve educational objectives. The leader is therefore expected to have sufficient expertise, abilities and skills.…”
Section: Introductionmentioning
confidence: 99%